Pengaruh Metode Storytelling dalam Meningkatkan Kemampuan Empati Anak Usia Dini - Wahyuni, Ajeng Sri; Qonita, Qonita; Mulyana, Edi Hendri (Darul Yasin Al Sys, 2024)
This article aims to determine the influence of the storytelling method in improving the empathy abilities of young children. One method that can be used to improve empathy skills in young children is the storytelling method. Through storytelling, children can take the values in the story and apply them to everyday life. This research uses a qualitative descriptive approach with a literature study method which contains a presentation of theories, findings and other research materials obtained to be used as a reference in this research. The literature source search method uses an electronic database from Goggle Scholar by focusing on articles that have similar discussions regarding the influence of the storytelling method in improving the empathy abilities of young children. Based on the discussion of the results of the literature study, all the articles referred to state that there is an increase in the empathy abilities of young children after implementing learning using the storytelling method and that this method is effective in increasing empathy abilities. Children's empathy abilities increase as indicated by children being able to implement the values contained in the story. In conclusion, the storytelling method influences children's empathy abilities from an early age by providing a positive and effective influence. Thus, the storytelling method can continue to be applied and developed to stimulate children's development.